Development of a Loop-Mediated Isothermal Amplification Method for the Rapid Detection of Phytopythium vexans - Wang, Tuhong; Ji, Haojun; Yu, Yongting; Wang, Xiaojie; Cheng, Yi; Li, Zhimin; Chen, Jia; Guo, Litao; Xu, Jianping; Gao, Chunsheng (Frontiers in Microbiology, 2021)
Brown root rot caused by Phytopythium vexans is a new destructive root disease on many plants such as Gingko, Citrus, kiwifruit, and ramie. The establishment of loop-mediated isothermal amplification (LAMP) technology for detecting P. vexans can help monitor and control brown root rot quickly, efficiently, and accurately. LAMP technology is known for its simplicity, sensitivity, and speed; and it does not require any specialized equipment - a water bath or a thermoblock is sufficient for isothermal amplifications. LAMP products can be visualized by using hydroxy naphthol blue (HNB) dye or agarose gel electrophoresis. In this study, by searching and comparing the internal transcribed spacer (ITS) sequences of P. vexans and the related species in oomycete genera Pythium, Phytopythium and Phytophthora, we designed specific primers targeting the ITS gene region of P. vexans. Using HNB dye, we established a LAMP technique for rapid detection of P. vexans by visible color change. In addition, we optimized the protocol to enhance both sensitivity and specificity for P. vexans detection. Under the optimized condition, our protocol based on LAMP technology could detect as low as 24 copies of the P. vexans genomic DNA, which is 100 times more sensitive than conventional PCR. This method can successfully detect P. vexans using cell suspensions from P. vexans - infected ramie root tissues.